Implementation of a new histological grading system in ovarian mucinous carcinomas and its association with the risk of recurrence: a retrospective cohort study - Yoshida, Adriana; Andrade, Liliana Aparecida Lucci De Angelo; Almeida, Ricardo Ruiz Garcia de; Machado, Helymar da Costa; Sarian, Luís Otávio; Derchain, Sophie (São Paulo Medical Journal, 2026)
BACKGROUND: This retrospective cohort study evaluated the prognostic significance of the Growth-Based Grade (GBG) system compared to International Federation of Gynecology and Obstetrics (FIGO) grading in ovarian mucinous carcinoma (OMC). Although FIGO grading is commonly used, its prognostic value remains controversial. The GBG system, which classifies tumors as low-grade (G1) or high-grade (G2) based on the proportion of infiltrative growth, has emerged as a potential prognostic tool. OBJECTIVES: To assess the prognostic significance of GBG and compare it with FIGO grading in OMC. DESIGN AND SETTING: This retrospective cohort study included 37 women with OMC treated at a single institution between 2009 and 2022. METHODS: GBG was determined by a histopathological review of hematoxylin and eosin-stained slides. Clinical and demographic data, including FIGO stage, CA125 levels, surgical procedures, and follow-up information, were collected. Kaplan-Meier analysis and Cox regression were used to assess the associations between GBG grading, FIGO stage, and survival outcomes. RESULTS: GBG 2 tumors were significantly associated with elevated CA125 levels, advanced FIGO stage (III), and bilaterality. Multivariate analysis showed that GBG 2 conferred a 5.4-fold higher risk of recurrence compared with GBG 1. While FIGO stage III was predictive of overall survival, FIGO grading was not associated with recurrence risk. CONCLUSION: This study suggests a potential prognostic value of the GBG system in mucinous ovarian carcinoma. GBG 2 tumors showed a higher risk of recurrence than GBG 1 tumors, whereas FIGO grading showed no such association. These findings align with previous reports and should be interpreted in the context of additional studies to clarify the system’s clinical relevance.